Simultaneous Voltammetric Determination of Amlodipine and Atorvastatin on Anodically Pretreated Boron-Doped Diamond Electrode - Rebech, Igor; Salamanca-Neto, Carlos Alberto Rossi; Scremin, Jessica; Sartori, Elen Romão (Orbital: The Electronic Journal of Chemistry, 2017)
An innovative electroanalytical method has been described for the simultaneous determination of amlodipine besylate (AML) and atorvastatin calcium (ATOR) using the square-wave voltammetry and an anodically pretreated boron-doped diamond electrode. Two very well-resolved and reproducible oxidation peaks for AML and ATOR were obtained in Britton-Robinson buffer solution (pH 4.0). Under the optimum analytical experimental conditions, the method exhibits linear responses to AML and ATOR in the concentration ranges 2.0 – 28 and 1.0 – 50 µmol L−1, respectively, with detection limits of 0.028 and 0.38 µmol L−1, respectively. The proposed novel method was applied in the simultaneous determination of AML and ATOR content in combined dosage forms and the accuracy was attested by means of comparison with those data obtained from high performance liquid chromatography at a 95% confidence level (paired t-test). DOI: http://dx.doi.org/10.17807/orbital.v9i4.973